Children of Formerly and Currently Incarcerated Parents in Iceland: Is Parental Incarceration a Predictor for Antisocial Behavior in Children? - Thelma Lind Smáradóttir 1991- (2018)
The purpose of this research study was to examine if parental incarceration is a predictor for antisocial behavior in children of formerly and currently incarcerated parents in Iceland. Based on previous research, children of incarcerated parents were expected to show greater antisocial behavior. In addition, parental support was expected to be a protective factor for antisocial behavior among said children. Participants were 10.783 Icelandic children, aged 12 to 18 years old, in 8th, 9th and 10th grade in elementary school. The overall response rate was 86.3%. A binary logistic regression showed that the odds of reporting antisocial behavior were higher for children of incarcerated parents, compared to their peers, and that parental support is a protective factor for antisocial behavior, but not for children of incarcerated parents. After the control variables; gender, family violence and sexual abuse, were added to the logistic regression model, as well as the independent variable; parental support, the odds for antisocial behavior were not significantly higher for children of incarcerated parents, compared to their peers. This indicates that the parental incarceration only explains a portion of the likelihood of antisocial behavior and that various other factors may contribute to antisocial behavior for these children. Keywords: parental incarceration, parental support, antisocial behavior, children, adolescents Markmið rannsóknarinnar var að skoða hvort fangelsisvist foreldra sé spáþáttur fyrir andfélagslegri hegðun hjá börnum fyrrverandi og núverandi fanga á Íslandi. Byggt á fyrri rannsóknum var búist við að börn fanga sýndu meiri andfélagslega hegðun. Þá var búist við að foreldrastuðningur væri sterkur verndandi þáttur fyrir andfélagslegri hegðun hjá börnum fanga. Þátttakendur voru 10.783 íslensk börn, á aldrinum 12 til 18 ára, í 8., 9. og 10. bekk í grunnskóla. Heildarsvarhlutfallið var 86,3%. Tvíundargreining sýndi fram á að líkur á andfélagslegri hegðun voru hærri hjá börnum fyrrum og núverandi fanga, ...